2014
DOI: 10.3233/bme-130949
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sr-substituted hydroxyapatite thin film by sputtering technique from mixture targets of hydroxyapatite and strontium apatite

Abstract: Sr-substituted hydroxyapatite thin films were prepared by sputtering technique from mixture targets of hydroxyapatite (HA) and strontium apatite (SrAp). The HA and SrAp powders were mixed at 0-100% Sr/(Sr + Ca) target ratios. The coated films were recrystallized by a hydrothermal treatment to reduce film dissolution. The films were then characterized by X-ray diffractometry (XRD), scanning electron microscopy (SEM) and inductively coupled plasma atomic emission spectrometry (ICP). The osteocompatiblity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
2
8
0
1
Order By: Relevance
“…50 In particular, Sr-HA samples were characterized by general peak broadening and shifts in low 2y angle peaks, which are typical evidences of ion substitution. 49 The analysis by FTIR further confirmed the findings of the XRD analyses: typical peaks and bands of phosphate and hydroxyl vibrations were detected both in HA and Sr-HA. In addition, a minor signal that can be ascribed to carbonate impurities was also identified.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…50 In particular, Sr-HA samples were characterized by general peak broadening and shifts in low 2y angle peaks, which are typical evidences of ion substitution. 49 The analysis by FTIR further confirmed the findings of the XRD analyses: typical peaks and bands of phosphate and hydroxyl vibrations were detected both in HA and Sr-HA. In addition, a minor signal that can be ascribed to carbonate impurities was also identified.…”
Section: Discussionsupporting
confidence: 75%
“…As Sr 2+ ions (ionic radius 1.18 Å) are substituted at Ca 2+ (0.99 Å) sites in the HA lattice structure, expansion in the unit cell occurs, which consequently results in peak broadening as well as slight shifting in peak position. 49 Lattice parameters obtained using Bruker's TOPAS software confirmed this observation. The software showed that the a-axis and c-axis parameters of Sr-HA were increased after the substitution of Sr 2+ , as presented in Table 3.…”
Section: Copper Complexation and Release From Copper(ii)chitosanmentioning
confidence: 63%
See 1 more Smart Citation
“…Sr-HA has been deposited both by Sr-HA targets with variable Sr/(Sr + Ca) ratio and by co-deposition from different targets. Deposition on titanium alloys and silicon has been reported [1,24,38,43]. Interestingly, the content of Sr was found to influence sputtering rate.…”
Section: Deposition By Magnetron Sputteringmentioning
confidence: 98%
“…From a biological point of view, Sr increases the mechanical strength of bone [21] and has an anti-osteoporotic effect [19][20][21]. In fact, strontium ranelate, a strontium-based drug used against osteoporosis, can boost osteoblast activity while inhibiting osteoclasts [20,21,24,37,38,42,43]. Sr capability to improve bone regeneration has also been demonstrated by tests in vivo [17,20,37,38,42].…”
Section: The Role Of Ionic Substitutions In Hydroxyapatitementioning
confidence: 99%